Jursprudentical and Legal Critique of “Tatarros” and “Avoidance of Taghut” in the Foundations of Takfiri Terrorism - shima esmaeilzadeh; Seyyed Hossein Hashemi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2021)
Takfiri terrorism, as a political phenomenon for those claiming power in form of religious groups is expanding in Islamic countries and has become the greatest challenge for the Islamic world. Misuse of jurisprudential rules named "Tatarros" and "Avoidance of Taghut" is the most abject mental and practical approach that is being practised by this group. The present article adopts library and descriptive-analytical methods to examine major principles of Takfiri terrorism from the perspective of jurisprudence and law. The purpose of this study is to prove that the main principles of Takfiri terrorism, namely the jurisprudential rule of "Tatarros" and "Avoidance of Taghut", seek aggression and other forms of terror in Islamic countries and that the killing of Muslims by Takfiris is unrelated to the rule of Tatarros. The question is what conditions govern these rules according to Islamic jurists and whether these rules entail suicide attacks and the killing of civilians.